Design Strategy for Tourism Object Management Case Study at Loken Barn Resort Karo District, North Sumatra Province - Arbaiyah, Arbaiyah; Mubarak, Husni (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Karo Regency is an area that has so many natural attractions. Loken Barn Resort at Pengambatan, Gajah Bobok Street, Merek District, Karo Regency, North Sumatra Province 22173, which is managed and developed by an owner of Loken Barn Resort. The purpose of this study is to analyze the owner's strategy in managing and developing the Loken Barn Resort location in Karo Regency. This type of research is descriptive qualitative research. Sources of research materials are key information and related information in this study. Data collection techniques in this study were observation, interview documentation, and literature study. Data analysis techniques used with data collection, data simplification, data presentation, and conclusions. The results of this study indicate that in managing and developing tourist destinations it is considered that it is still not optimal in the management and development of Loken Barn Resort attractions due to limited professional staff and human resources and the lack of budget to manage and develop Loken Barn Resort attractions.